Proceedings of the International Conference on Information Economy, Data Modeling and Cloud Computing, ICIDC 2022, 17-19 June 2 2022
DOI: 10.4108/eai.17-6-2022.2322799
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Gold Price for the First 20 Years in the 21st Century with Random Walk Model

Abstract: Whether or not a stock index can be interpreted by the random walk model is important but debatable because it is closely linked to the weak form of the efficient market hypothesis (EMH). As an important commodity, a precious metal, and the reserve in central banks, the gold price is the objective of numerous studies. The issue of whether the gold price is subject to the weak form of EMH is interesting and important. Although the gold price is the oldest recorded price in human history, we select the first 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As seen in Figure 4, it was observed that the highest generated publications were 19 publications in 2020, followed by 14 publications in 2014 and 2016, then 13 documents in 2019, and 12 documents in 2021. However, there are limited publications found on the installation of marine hoses [160][161][162][163][164][165][166][167][168][169][170] compared to other marine systems [171][172][173][174][175][176][177][178][179][180].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in Figure 4, it was observed that the highest generated publications were 19 publications in 2020, followed by 14 publications in 2014 and 2016, then 13 documents in 2019, and 12 documents in 2021. However, there are limited publications found on the installation of marine hoses [160][161][162][163][164][165][166][167][168][169][170] compared to other marine systems [171][172][173][174][175][176][177][178][179][180].…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Figure 4, it was observed that the highest generated publications were 19 publications in 2020, followed by 14 publications in 2014 and 2016, then 13 documents in 2019, and 12 documents in 2021. However, there are limited publications found on the installation of marine hoses [160][161][162][163][164][165][166][167][168][169][170] compared to other marine systems [171][172][173][174][175][176][177][178][179][180]. As observed in Figure 5a, the highest publications by subject area were in engineering, with 212 publications (42.7%), energy, with 99 publications (19.9%), earth and planetary sciences, with 46 publications (9.3%), environmental science with 23 publications (7.4%), chemical engineering with 23 publications (4.6%), materials science with 21 publications (4.2%), and agricultural and biological sciences with 16 publications (3.2%), among other subject areas.…”
Section: Resultsmentioning
confidence: 99%